BAHAN AJAR ELEKTRONIK GLOBAL WARMING BERBASIS INKUIRI DENGAN PENDEKATAN KETERAMPILAN BERFIKIR KRITIS - Wayan Suwatra; Agus Suyatna (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The learning process is a series of interrelated multiple systems with one another. The use of media in the learning process is expected to help teachers make it easier to teach the material to students. One medium that can be used in the learning process in schools is an electronic-based teaching materials. The purpose of this research is mengembangakan inquiry-based electronic teaching materials to improve students' critical thinking process to analyze and sum up the essence of the subject of global warming. Method development using the R & D of Borg & Gall, combined with the ADDIE model of media development. With the test subject teachers and students at SMAN 9 Bandar Lampung. Data were collected through global warming competency test and a questionnaire about the needs of electronic teaching materials, were analyzed quantitatively and qualitatively. , Provided that the students 'understanding of global warming material is not maximized and one of the efforts to improve students' competence necessary teaching materials to the inquiry approach that encourages students to think critically in electronic form. Keywords: electronic instructional materials, global warming, based inquiry, critical thinking skills.